STUDYING ETHNIC STEREOTYPES AND PSYCHOLOGICAL STANDARDS IN PREPARING GIRLS FOR A FAMILY - Dzhukhonova Nokhida Khayotzhonovna (World Scientific Research Journal, 2025)
Annotation: This article systematizes socio-psychological approaches, forms, methods and means aimed at identifying ethnic stereotypes and psychological institutions in preparing girls for a family. It is proved that ethnic stereotypes and psychological institutions of regional girls, social values, interpersonal emotional and cognitive components of behavior have ethnic significance, are socio-psychological characteristics that optimize the level of readiness for family life.